2024
DOI: 10.3389/fendo.2023.1248934
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and metabolic syndrome and complications: association, mechanism, and translational applications

Dongmei Zhou,
Peipei Lu,
Xianglai Mo
et al.

Abstract: Metabolic syndrome is a medical condition characterized by several metabolic disorders in the body. Long-term metabolic disorders raise the risk of cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM). Therefore, it is essential to actively explore the aetiology of metabolic syndrome (MetS) and its comorbidities to provide effective treatment options. Ferroptosis is a new form of cell death that is characterized by iron overload, lipid peroxide accumulation, and decreased glutathione peroxidase 4(G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 167 publications
0
2
0
Order By: Relevance
“…Recently, studies have revealed the harmful effects of iron, specifically ferroptosis, which can lead to renal tissue damage [27][28][29]. Hu et al conducted experiments using cisplatin-injected mice to create an AKI model and found that the ferroptosis inhibitor Fer-1 significantly reduced serum urea nitrogen and creatinine levels, thereby alleviating renal damage [10].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have revealed the harmful effects of iron, specifically ferroptosis, which can lead to renal tissue damage [27][28][29]. Hu et al conducted experiments using cisplatin-injected mice to create an AKI model and found that the ferroptosis inhibitor Fer-1 significantly reduced serum urea nitrogen and creatinine levels, thereby alleviating renal damage [10].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, high iron levels may contribute to the continuous release of adipokines and promote an inflammatory environment, redirecting immune responses and promoting obesity occurrence [ 14 ]. Obesity-related persistent inflammation is characterized by the disproportionate release of FFAs and proinflammatory cytokines from adipocytes; this has led to the hypothesis of a connection between obesity and ferroptosis [ 15 ]. Ferroptosis, which was identified in 2012, is an iron-dependent cell death mechanism that is distinct from apoptosis, necrosis, and other cellular death mechanisms.…”
Section: Introductionmentioning
confidence: 99%